Determinan Permintaan Bahan Bakar Minyak Pertamini di Kabupaten Banyumas : Perspektif Central Place Theory - Nur Avita Fardiani; Herman Sambodo; bambang bambang (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
The aim of this study is to analize the effect of income, pertalite fuel prices at pertamini, pertalite fuel prices at pertamina, job mobilization, and location on pertalite fuel demand of pertamini and to find out the variables that most influence pertalite fuel demand in pertamini. Respondents from this study are 100 people as sample form three regions which were used as research sites in Banyumas regency in accordance with central place theory characteristics. The technique of conveying data uses the interview and questionnaire method while for the analysis technique uses multiple linear regression techniques. The results of this study indicate that income, job mobilization and location are significant for pertalite fuel demand in Pertamini, while pertalite fuel prices in Pertamini and pertalite fuel prices in Pertamina are not related to pertalite fuel demand in Pertamini. The most influence variable to the pertalite fuel demand in Pertamini is household income. Inequality of Pertamina gas stations is the main problem in fuel demand, so the implication of this research is government should make regulations to support the development of Pertamina gas stations by entrepreneurs to be more distributed or regulations that support development of Pertaminas Pertashop which has legal status so that society will be more prosperous because the fuel needs are met with more affordable prices and locations.